UPAYA PENINGKATAN KEPEDULIAN KEBERSIHAN PANTAI MELALUI MANAJEMEN EFEKTIF PROGRAM EDUKASI LINGKUNGAN DI PELABUHAN MERAK KOTA CILEGON - Tabroni, Tabroni; Bahits, Abdul; Lesmana, Ihwan Satria; Saepudin, Saepudin; Harsono, Pramudi; Yuliah, Yuliah (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
Community service activities with a focus on efforts to increase awareness of beach cleanliness at Merak Harbor, Cilegon City, through effective management of environmental education programs. Evaluation of activities revealed significant problems related to organic waste, especially wood and large tree trunks, at Merak Harbor Beach. As a solution, it is recommended to use heavy equipment in the cleaning process, to achieve optimal effectiveness and efficiency. In addition, the potential for using organic waste as raw material for wooden crafts or as an alternative energy source was also identified. Follow-up implementation of these recommendations can have a positive impact on the sustainability of future beach clean-up efforts. It is hoped that the results of this service activity will not only create environmental awareness, but also provide concrete and sustainable solutions to beach cleanliness problems. Through the integration of these practical suggestions in the next beach clean-up action, it is hoped that the community can be actively involved in maintaining beach cleanliness, while utilizing the positive potential of organic waste for sustainable local economic activities